Revitalisasi Pendidikan Agama Hindu di Era Digital: Upaya Membangun Karakter Religius Generasi Muda Hindu - Astuti, Ketut Widi; Tariani, Niluh; Eldayani, Wayan; Arta, I Gede; Gitayani, Komang Septy (Pratyaksa: Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2025)
This study aims to analyze and formulate strategies for revitalizing Hindu Religious Education in the digital era as an effort to build the religious character of Hindu youth. The paradigm shift in education due to the digital revolution and the globalization of values demands innovation in delivering religious teachings to remain relevant to modern life. Using a qualitative-descriptive approach, this research highlights the importance of transforming methods, media, and values in Hindu religious education to address the declining religiosity and spirituality among young people. The findings indicate that the use of digital technology such as e-learning, social media, and Hindu religious applications can serve as an effective tool to strengthen students’ understanding and spiritual experience. However, technological utilization must be balanced with the enhancement of religious digital literacy and the internalization of dharmic values to prevent religious superficiality, where religion is understood merely as symbols or digital content. Hindu religious teachers hold a strategic role as facilitators and digital spiritual guides, helping students integrate the teachings of Tat Tvam Asi, Karma Phala, and Ahimsa into both their digital and social lives. By emphasizing value-based pedagogy and reflective learning, the revitalization of Hindu Religious Education in the digital era has the potential to nurture a generation that is digitally literate yet spiritually grounded. The integration of Hindu philosophy, technology, and modern education becomes the key to shaping Hindu individuals who embody dharma able to maintain balance between knowledge, morality, and spirituality amidst the dynamics of social change.